IMPLEMENTATION OF TOPSIS METHOD AS A DECISION-MAKING MODEL IN CHOOSING A DEPARTMENT AT AL KHAIRIYAH CITANGKIL INTEGRATED ISLAMIC VOCATIONAL SCHOOL - Swastika, Rulin; Rohman, Efi (Jurnal TAM (Technology Acceptance Model), 2024)
In today's technological era, information technology is developing rapidly. One of them is in the field of education, currently many learning media have used technology as a means to facilitate it. With fundamental changes in the field of information and communication technology, information has now become a very valuable commodity and determines success. The problem raised this time is how to determine the majors of new students at Al Khairiyah Citangkil Integrated Islamic Vocational School. In solving this problem, the method that will be used to help select majors at Al Khairiyah Citangkil Integrated Islamic Vocational School is the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. This TOPSIS method is based on the concept where the best selected alternative not only has the shortest distance from the positive ideal solution, but also has the longest distance from the negative ideal solution. The TOPSIS method also has a simple and relatively easy-to-understand concept, efficient computation, and has the ability to measure the relative performance of each decision alternative in a simple mathematical form. The application of major selection using the TOPSIS method is very helpful in selecting majors to be more accurate, save time and get faster results. The decision support system for choosing a major at Al Khairiyah Citangkil Integrated Islamic Vocational School can be developed by creating a website-based system with variables of Psychometric Test Score, Al-Quran Test Score, Verbal Test Score, Basic Computer Test Score, Mathematics National Examination Score, Science National Examination Score, English National Examination Score, Indonesian National Examination Score, Parental Income where each test result is directly connected to the decision support database to produce accurate data.